Dendritic cell-based immunotherapy (DCVAC/OvCa) combined with second-line chemotherapy in platinum-sensitive ovarian cancer (SOV02): A randomized, open-label, phase 2 trial - Cibula, David; Rob, Lukas; Mallmann, Peter; Knapp, Pawel; Klat, Jaroslav; Chovanec, Josef; Minar, Lubos; Melichar, Bohuslav; Hein, Alexander; Kieszko, Dariusz; Pluta, Marek; Spacek, Jiri; et al. (Gynecologic oncology, 2021)
OBJECTIVE: DCVAC/OvCa is an active cellular immunotherapy designed to stimulate an immune response against ovarian cancer. We explored the safety and efficacy of DCVAC/OvCa plus carboplatin and gemcitabine in platinum-sensitive ovarian cancer. METHODS: In this open-label, parallel-group, phase 2 trial (ClinicalTrials.gov number NCT02107950), patients with platinum-sensitive ovarian cancer relapsing after first-line chemotherapy were randomized to DCVAC/OvCa and chemotherapy or chemotherapy alone. DCVAC/OvCa was administered every 3-6 weeks (10 doses). Endpoints included safety, progression-free survival (PFS; primary efficacy endpoint) and overall survival (OS; secondary efficacy endpoint). RESULTS: Between November 2013 and May 2015, 71 patients were randomized to chemotherapy in combination with DCVAC/OvCa or to chemotherapy alone. Treatment-emergent adverse events related to DCVAC/OvCa, leukapheresis and chemotherapy occurred in six (16.2%), two (5.4%), and 35 (94.6%) patients in the DCVAC/OvCa group. Chemotherapy-related events occurred in all patients in the chemotherapy group. Seven patients in the DCVAC/OvCa group were excluded from primary efficacy analyses due to failure to receive ≥1 dose of DCVAC/OvCa. PFS was not improved (hazard ratio [HR] 0.73, 95% confidence interval [CI] 0.42-1.28, P = 0.274, data maturity 78.1%). Median OS was significantly prolonged (by 13.4 months) in the DCVAC/OvCa group (HR 0.38, 95% CI 0.20-0.74, P = 0.003; data maturity 56.3%). A signal for enhanced surrogate antigen-specific T-cell activity was seen with DCVAC/OvCa. CONCLUSIONS: DCVAC/OvCa combined with chemotherapy had a favorable safety profile in patients with platinum-sensitive ovarian cancer. DCVAC/OvCa did not improve PFS, but the exploratory analyses revealed OS prolongation and enhanced surrogate antigen-specific T-cell activity.
Keywords: dospělí; Carcinoma, Ovarian Epithelial; nádory vaječníků; Immunogenic cell death; Female; kombinovaná terapie; Adult; ženské pohlaví; Dendritic Cells; Deoxycytidine; dendritické buňky; Immunotherapy, Adoptive; gemcitabin; lidé; imunoterapie adoptivní; staging nádorů; epiteliální ovariální karcinom; Ovarian Neoplasms; Ovarian cancer; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; Carboplatin; protokoly protinádorové kombinované chemoterapie; deoxycytidin; Combined Modality Therapy; Aged; Gemcitabine; karboplatina; Dendritic-cell based immunotherapy; lidé středního věku; senioři nad 80 let; senioři; Middle Aged; Neoplasm Staging; Humans